2012
DOI: 10.1007/s00125-012-2692-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of modified LDL-induced pericyte loss and retinal injury in diabetic retinopathy

Abstract: Aims/hypothesis In previous studies we have shown that extravasated, modified LDL is associated with pericyte loss, an early feature of diabetic retinopathy (DR). Here we sought to determine detailed mechanisms of this LDL-induced pericyte loss. Methods Human retinal capillary pericytes (HRCP) were exposed to ‘highly-oxidised glycated’ LDL (HOG-LDL) (a model of extravasated and modified LDL) and to 4-hydroxynonenal or 7-ketocholesterol (components of oxidised LDL), or to native LDL for 1 to 24 h with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 53 publications
(50 reference statements)
12
125
1
3
Order By: Relevance
“…In a study of the prevalence of and risk factors for diabetic retinopathy in people with newly diagnosed type 2 diabetes mellitus using Scottish national data, diabetic retinopathy was associated with male sex, systolic blood pressure, time to screening and obesity [27]. In terms of dyslipidaemia, intraretinal modified LDLs have been implicated in diabetic retinopathy, and it has been shown that extravascular modified LDLs may promote retinal pigment epithelium injury through oxidative stress, endoplasmic reticulum autophagy and apoptosis, whereas modified HDLcholesterol had protective effects [28,29]. The same holds true for other novel risk markers such as serum apolipoprotein AI [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the prevalence of and risk factors for diabetic retinopathy in people with newly diagnosed type 2 diabetes mellitus using Scottish national data, diabetic retinopathy was associated with male sex, systolic blood pressure, time to screening and obesity [27]. In terms of dyslipidaemia, intraretinal modified LDLs have been implicated in diabetic retinopathy, and it has been shown that extravascular modified LDLs may promote retinal pigment epithelium injury through oxidative stress, endoplasmic reticulum autophagy and apoptosis, whereas modified HDLcholesterol had protective effects [28,29]. The same holds true for other novel risk markers such as serum apolipoprotein AI [30].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the literature shows that oxidative stress, implicated in pericyte loss, may be induced also by extravasated, modified plasma LDL, present in the diabetic but not the healthy retina [119,120].…”
Section: Pericyte Loss During Dr: Glucose Metabolism Pathwaysmentioning
confidence: 99%
“…Pericyte viability was determined in 96-well plates (1 × 10 4 cells/well) using the Cell Counting Kit-8 (CCK-8; Dojindo Molecular Technologies, Rockville, MD) ( 15 ).…”
Section: Cell Viabilitymentioning
confidence: 99%